2006
DOI: 10.1093/aje/kwj199
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Sleep Characteristics among Early-Middle-Aged Adults

Abstract: Despite mounting evidence that sleep duration is a risk factor across diverse health and functional domains, little is known about the distribution and determinants of sleep. In 2003-2004, the authors used wrist activity monitoring and sleep logs to measure time in bed, sleep latency (time required to fall asleep), sleep duration, and sleep efficiency (percentage of time in bed spent sleeping) over 3 days for 669 participants at one of the four sites of the Coronary Artery Risk Development in Young Adults (CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
391
7
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 513 publications
(457 citation statements)
references
References 33 publications
55
391
7
4
Order By: Relevance
“…Habitual sleep duration was assessed at home by actigraphy using the Actiwatch (Mini-Mitter, Bend, OR) in accordance with previously described methods (23)(24)(25). Participants were asked to wear the Actiwatch for 5 consecutive days-3 weekdays and 2 weekend days-and to maintain their habitual bedtimes and fill out daily sleep logs.…”
Section: Actigraphymentioning
confidence: 99%
“…Habitual sleep duration was assessed at home by actigraphy using the Actiwatch (Mini-Mitter, Bend, OR) in accordance with previously described methods (23)(24)(25). Participants were asked to wear the Actiwatch for 5 consecutive days-3 weekdays and 2 weekend days-and to maintain their habitual bedtimes and fill out daily sleep logs.…”
Section: Actigraphymentioning
confidence: 99%
“…A study conducted between 1990 and 1994 found that participants slept on average 6.2 h per night, as measured with wrist actigraphy (11). Recently, in the Coronary Artery Risk Development in Young Adults Sleep Study (2000)(2001)(2002)(2003)(2004)(2005)(2006), sleep duration derived from several days of wrist actigraphy averaged 6.1 h per night (12), whereas self-reported sleep averaged 6.7 h per weeknight and 7.3 h per weekend night (13). Declines in sleep time can be attributed, in part, to extended work schedules including shift work, long commuting times, stressful lifestyles, modern conveniences such as 24-h television and computer/Internet use, and social and leisure activities.…”
Section: Epidemiologic Evidence For a Link Between Sleep Disturbancesmentioning
confidence: 99%
“…Several authors, including the American Academy of Sleep Medicine's Standards of Practice Committee, view actigraphy as a reliable method for assessing sleepwake patterns in adults. [11][12][13][14][15] Lauderdale et al 16 collected actigraphy data over two 3-day periods for 669 participants aged 38-50 years in the CARDIA Study. They demonstrated substantial discrepancies between self-reported and actigraphically measured sleep duration.…”
Section: Introductionmentioning
confidence: 99%